Implementing voluntary medical male circumcision using an innovative, integrated, health systems approach: experiences from 21 districts in Zimbabwe. Issue 1 (1st January 2018) - Feldacker, Caryl; Makunike-Chikwinya, Batsirai; Holec, Marrianne; Bochner, Aaron F.; Stepaniak, Abby; Nyanga, Robert; Xaba, Sinokuthemba; Kilmarx, Peter H.; Herman-Roloff, Amy; Tafuma, Taurayi; Tshimanga, Mufuta; Sidile-Chitimbire, Vuyelwa T.; et al.
ABSTRACT: Background : Despite increased support for voluntary medical male circumcision (VMMC) to reduce HIV incidence, current VMMC progress falls short. Slow progress in VMMC expansion may be partially attributed to emphasis on vertical (stand-alone) over more integrated implementation models that are more responsive to local needs. In 2013, the ZAZIC consortium began implementation of a 5-year, integrated VMMC program jointly with Ministry of Health and Child Care (MoHCC) in Zimbabwe. Objective : To explore ZAZIC's approach emphasizing existing healthcare workers and infrastructure, increasing program sustainability and resilience. Methods: A process evaluation utilizing routine quantitative data. Interviews with key MoHCC informants illuminate program strengths and weaknesses. Methods : A process evaluation utilizing routine quantitative data. Interviews with key MoHCC informants illuminate program strengths and weaknesses. Results : In start-up and year 1 (March 2013–September, 2014), ZAZIC expanded from two to 36 static VMMC sites and conducted 46, 011 VMMCs; 39, 840 completed from October 2013 to September 2014. From October 2014 to September 2015, 44, 868 VMMCs demonstrated 13% increased productivity. In October, 2015, ZAZIC was required by its donor to consolidate service provision from 21 to 10 districts over a 3-month period. Despite this shock, 57, 282 VMMCs were completed from October 2015 to September 2016 followed by 44, 414 VMMCs in only 6 months, from October 2016 to March 2017. Overall, ZAZIC performed 192, 575 VMMCs from March 2013 to March, 2017. The vast majority of VMMCs were completed safely by MoHCC staff with a reported moderate and severe adverse event rate of 0.3%. Conclusion : The safety, flexibility, and pace of scale-up associated with the integrated VMMC model appears similar to vertical delivery with potential benefits of capacity building, sustainability and health system strengthening. These models also appear more adaptable to local contexts. Although more complicated than traditional approaches to program implementation, attention should be given to this country-led approach for its potential to spur positive health system changes, including building local ownership, capacity, and infrastructure for future public health programming.